2016
DOI: 10.1111/aswp.12106
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance as a Development and Poverty Alleviation Tool in Rural Bangladesh: A Critical Assessment

Abstract: Poverty is multidimensional in nature and exists in every part of the world. Microfinance is considered one of the most important programs to achieve poverty reduction, particularly in Bangladesh. It has been estimated that nearly 45% of Bangladesh's population lives below the poverty line. This qualitative research study was conducted in order to determine the effectiveness of microfinance programs and the contributing factors to the high-level of poverty among microfinance beneficiaries in the district of Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
0
23
0
8
Order By: Relevance
“…Credit dispersal in the SHGs was based on need and priority, that is, the member with the most urgent need, as decided by the president, was given priority over other applicants. Previous studies have indicated that this approach of deciding upon beneficiaries sometimes results in biased decisions (Ali, Hatta, Azman, & Islam, ). Payment of school fees, medical treatment, marriage, and housing construction were the main reasons cited by members for needing a loan.…”
Section: Resultsmentioning
confidence: 99%
“…Credit dispersal in the SHGs was based on need and priority, that is, the member with the most urgent need, as decided by the president, was given priority over other applicants. Previous studies have indicated that this approach of deciding upon beneficiaries sometimes results in biased decisions (Ali, Hatta, Azman, & Islam, ). Payment of school fees, medical treatment, marriage, and housing construction were the main reasons cited by members for needing a loan.…”
Section: Resultsmentioning
confidence: 99%
“…She also reported the demining behaviour of the field officers (Karim, 2011). Ali et al, (2017) carried out another extensive research on the borrowers of BRAC, ASA and Proshika in Bogra district of Bangladesh. They found ineffective performances of these organizations.…”
Section: Similarities With Others Researchesmentioning
confidence: 99%
“…In some cased, mismanagement, unskilled and corrupted field staffs were held responsible for mistreating the poor beneficiaries (I. Ali et al, 2017). Another empirical study recently carried out in Satkhira district of Bangladesh.…”
Section: Similarities With Others Researchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, if microcredit can provide better access to institutional credit, it can help rural households manage risks and acquire inputs, including technology, to modernize agriculture and improve farm/nonfarm linkages [25]. Otherwise, microfinance may be unable to achieve poverty reduction [51][52][53][54] because of possible high interest rates, insufficient loans, unproductive use of loans, or even corruption and poor skills of microfinance institution staff [54]. Obviously, severe financial repression still exists in rural and poverty-stricken areas.…”
Section: Introductionmentioning
confidence: 99%